Analisis Efektivitas Pengelolaan Keuangan dan Implikasinya Terhadap Masyarakat Desa - Chairul Iksan Burhanuddin; Syamsuddin Syamsuddin; Maryam Nurdin; Fifi Nur Afifah Ibrahim; Rismayanti Rismayanti (Politeknik Ganesha Medan, 2022)
The objective of this research is to evaluate how well financial management works and what that means for society. With up to 8 informants, including members of the government and the community, this sort of research use qualitative approaches. The information gathered through interviews and the documentation of the data analysis methods applied were descriptive and provided a thorough explanation of the research theme. The findings of this study show that the Su'rulangi Village government's financial management and implementation are in accordance with applicable regulations and criteria. This can be seen through planning, implementation, reporting, administration, and accountability, while the implementation can be seen from the communication factor and resource factor. Disposition factors and bureaucratic factors for the effectiveness of the financial management of the Village Fund are disposition factors and bureaucratic factors. The Su'rulangi Village government implements the effects on the local economy through the Village Fund budget by offering benefits such as seed assistance, plant sprayers, water pumping machines, and assistance for farmers dealing with COVID-19 in the form of Direct Cash Assistance (BLT) and assistance. Other strategies rural areas can employ to strengthen their economies